Jundiá: efeitos fisiológicos do óleo essencial de Lippia alba adicionado à ração - Souza, Carine de Freitas (2014)
The aim of this study was to evaluate the effect of the essential oil of Lippia alba (EOLA) as a feed additive on ionoregulatory and metabolic parameters, and pituitary hormones expression in silver catfish, Rhamdia quelen. Fish were fed for 20 days with different concentrations of EOLA (0.0 control, 0.25 and 0.50 mL kg-1 food). Plasma Na+, Cl- , K+ and cortisol, and metabolic parameters were not affected by the diet, with the exception of ALT (alanine aminotransferase), which was higher in the liver of fish fed 0.50 mL EOLA kg-1 food. Fish fed 0.25 mL EOLA kg-1 food presented higher Na+/K+-ATPase activity and somatolactin expression, but H+-ATPase activity and growth hormone and prolactin expression did not change. The EOLA can be used as a dietary supplement for silver catfish at the evaluated concentrations, but using 0.25 mL EOLA kg-1 food seems to be more suitable than 0.50 mL EOLA kg-1 food since the latter may be related to liver damage.